Scoping Review: Why is Public Health Integrated into Medical Education? - Duarsa, Artha Budi Susila; Anulus, Ayu; Zoraya, Sabrina Intan (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Medical students who get community-involved medical education will be better equipped to address the health needs of their communities by integrating public health services into their practice. The importance of public health disciplines for physicians needs to be reinforced in the medical curriculum. Many studies, findings, and discussions report on the importance of this integration. This study aims to identify, decipher, and map the available scientific evidence regarding the importance of public health integration in medical education. Subjects and Method: This was a scoping review study using PUBMED, ProQuest, SCOPUS, Google Scholar, and other related sources. The keywords used in article searches are as follows: